Combination of high-pressure homogenization and ultrasound improves physiochemical, interfacial and gelation properties of whey protein isolate. (October 2020) - Shi, Ruijie; Liu, Yue; Hu, Jialun; Gao, Hao; Qayum, Abdul; Bilawal, Akhunzada; Munkh-Amgalan, G.; Jiang, Zhanmei; Hou, Juncai
Abstract: The main purpose of this work was to investigate the influence of high-pressure homogenization (HPH, 60, 90, and 120 MPa, three cycles) combined with ultrasound (US, 120, 360, and 600 W, 30 min) on the physiochemical, interfacial, and gelation properties of whey protein isolate (WPI). Compared with an individual application of HPH or US, a combined HPH-US treatment can further reduce average particle size (D4, 3 ) and turbidity of WPI, while significantly ameliorating its surface hydrophobicity, fluorescence intensity, and free sulfhydryl content. Compared with that of an untreated WPI, the emulsifying ability index (EAI) of WPI was increased by 8.54% after a 120 MPa HPH and by 7.63% after a 600 W US, whereas it increased by 13.97% after a combined treatment of 120 MPa and 600 W HPH-US. Accordingly, the foaming ability (FA) and the foaming stability (FS) were enhanced by 26.10% and 118.18% at 120 MPa and 600 W, respectively. The hardness of WPI gel was also increased by 170.45% at 120 MPa and 600 W compared to the untreated WPI. Therefore, the combination of HPH and US could make a remarkable improvement in the physicochemical functional characteristics of WPI, providing basic data support for the food industry to obtain excellent novel WPI ingredients. Highlights: HPH-US combined treatment effectively enhanced foaming properties of WPI. Emulsifying ability index of WPI was enhanced by 13.97% at 120 MPa and 600 W of treatment. Hardness of WPI gel was increased by 170.45% at 120 MPa and 600 W of treatment.